1991
DOI: 10.1111/j.1365-2605.1991.tb01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Male fertility in long‐term survivors of childhood acute lymphoblastic leukaemia

Abstract: To study long-term testicular function following the treatment of acute lymphoblastic leukaemia (ALL) in childhood, 37 young adult males were assessed at two separate time points. The initial assessment was made by a wedge testicular biopsy after completion of treatment (median 9.7 years; range 4.1-16.3 years) and the subsequent assessment (median 18.6 years; range 15.4-26.8 years) consisted of the clinical examination of pubertal stage, measurement of serum gonadotrophins and testosterone and, in 19 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 18 publications
4
54
1
1
Order By: Relevance
“…Several studies have shown an impaired gonadal function in adult male survivors of childhood cancer [4,5]. Post-treatment gonadal damage showed to be depending on the type of used agents and cumulative dosages administered during childhood [6][7][8]. Usually, studies were based on one type of malignancy and treatment protocol and had limited number of survivors included [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown an impaired gonadal function in adult male survivors of childhood cancer [4,5]. Post-treatment gonadal damage showed to be depending on the type of used agents and cumulative dosages administered during childhood [6][7][8]. Usually, studies were based on one type of malignancy and treatment protocol and had limited number of survivors included [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Post-treatment gonadal damage showed to be depending on the type of used agents and cumulative dosages administered during childhood [6][7][8]. Usually, studies were based on one type of malignancy and treatment protocol and had limited number of survivors included [6][7][8]. Age at time of treatment was suggested to give some protection against chemotherapy induced gonadal damage due to quiescent stage of the testis in the prepubertal age [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, more than half of the long-term survivors are not infertile and do not need to preserve spermatogonial stem cells (3,4). Alkylating agents and radiation therapy for testes are high-risk factors for infertility (4,28,29), but patients who need radiation therapy as a pretreatment for bone marrow transplantation have, among childhood leukemic patients, poor prognoses (30) and are in the minority of patients with childhood leukemia. This procedure should be strictly limited to candidates for preservation of spermatogonial stem cells.…”
Section: Figurementioning
confidence: 99%
“…Male infertility is one of these major effects (1-3), but little is known about the mechanisms by which chemotherapeutic agents used to treat childhood cancer damage spermatogenesis in the prepubertal human testis. Permanent tubular damage may first become apparent during puberty when size of the testis remains prepubertal and sperm production does not initiate (1,4). The lack of appropriate methodology for detecting early cytotoxic damage to the immature testis has made it difficult to identify the exact maturational events on which these anticancer drugs exert their gonadotoxicity.…”
Section: Introductionmentioning
confidence: 99%